Development of a PjBL-STEM-Based IPAS Project Learning Program Oriented Toward Deep Learning to Enhance Vocational Students' Creativity and Performance Skills - Cahyawati, Arlik; Suyatna, Agus; Rosidin, Undang; Herlina, Kartini; Distrik, I Wayan (Universitas Islam Negeri Raden Intan Lampung, 2026)
This study aims to develop and evaluate a Project-Based Learning integrated with STEM (PjBL-STEM) learning program oriented toward deep learning principles—encompassing mindful, meaningful, and joyful learning—within the IPAS (Natural and Social Sciences) subject for tenth-grade vocational high school students. Motivated by the persistent gap between conventional instructional practice and the competency demands of Industry 4.0, the study developed a structured instructional package consisting of a Deep Learning Lesson Plan (Perencanaan Pembelajaran Mendalam/PPM), student worksheets (LKPD), and supporting handouts, all anchored in the PjBL-STEM framework applied to electromagnetic induction as a sustainable energy technology context. The research employed a mixed-method approach guided by the four-stage 4D instructional development model (Define, Design, Develop, Disseminate). The study involved two classes of tenth-grade students enrolled in the Electrical Power Installation Engineering program (X TITL-1 as experimental group; X TITL-2 as control group) at a public vocational high school in Bandar Lampung during the 2025/2026 academic year. Expert validation by three specialists yielded an overall validity score of 91.9% for the lesson plan and 91.5% for the student worksheets and handouts, both classified as highly valid. Teacher practicality evaluation indicated an overall score of 90.7%, categorized as excellent. Effectiveness analysis using the normalized gain (N-Gain) index revealed that the experimental group achieved a mean N-Gain of 0.90 (high category) for performance skills and 1.00 (high category) for creativity, compared with 0.30 and 0.45, respectively, for the control group receiving conventional instruction. These findings establish that integrating PjBL-STEM with deep learning principles produces a valid, practical, and effective instructional framework capable of significantly enhancing vocational students' creativity and practical performance competencies relevant to contemporary technological challenges.